Synthesis Of Thermo-Magneto-Responsive Poly(N-Isopropylacrylamide)-Based Composite Hydrogels For Adsorption-Desorption Of Chromium (Iii) Ions - Chen, Jian Jie (2019)
Stimuli-responsive composite hydrogels have been in the vanguard of researches for their application in metal ion adsorption and its release via conformational change. The preparation of composite hydrogels with both thermo- and magneto-responsiveness requires careful layer-by-layer coatings of functional shells onto the core of iron oxide magnetic nanoparticles (MNPs). However, multiple stages of shell encapsulation of MNPs remains a major setback on the production of composite hydrogels with adequate colloidal stability and well-functioned dual-responsiveness. In this study, homo-polymeric poly(N-isopropylacrylamide)-encapsulated magnetite nanoparticles (PNIPAM-MNPs) cross-linked composite hydrogels were facilely synthesized via layer-by-layer coatings with and without employing silanization precursor, 3-(trimethoxysilyl)propyl methacrylate (MPS). It was found that PNIPAM could be gelated directly onto the silica-coated, poly(vinylpyrrolidone) (PVP) functionalized MNPs (silica-PVP-MNPs) via free radical polymerization without MPS to improve its colloidal stability and both thermo-magneto-responsive. Besides, co-polymeric poly(N-isopropylacrylamide-co-acrylic acid)-encapsulated MNPs ((PNIPAM-co-AA)-silica-PVP-MNPs) composite hydrogels were prepared for elucidating the difference in adsorption mechanisms between chelating groups of carboyxlates (-COO-) contained by AA moiety and amides (-CONH) of NIPAM moiety. In the temperature manipulated adsorption-desorption tests, desorption of Cr3+ gradually predominated as temperature increased from 298 K to 323 K for PNIPAMsilica-PVP-MNPs. Re-adsorption of Cr3+ by the composite hydrogel took place as being quenched to 298 K for lower initial Cr3+ concentration (20 – 80 mg L-1) which showed that desorption can be realised for surface adsorption. Before heating, the equilibrium adsorption data of Cr3+ fitted well into Flory-Huggins and Frumkin models, that elucidated the chelation of Cr3+ ions occurred via replacement of water molecules on the binding sites. Moreover, PNIPAM-silica-PVP-MNPs had higher maximum adsorption capacity, qm (434.78 mg g-1) compared to (PNIPAM-co-AA)-silica-PVP-MNPs (qm = 243.90 mg g-1) as extrapolated by Langmuir isotherm model in which the data of both composite hydrogels also showed good fit to the model. The adsorption kinetic analysis indicated that Cr3+ adsorption on PNIPAM-silica-PVP-MNPs was governed by intra-particle diffusion and reversible surface physisorption as its data followed pseudo-first, pseudo-second- and intra-particle diffusion models. On the other hand, surface chemisorption predominated over (PNIPAM-co-AA)-silica-PVP-MNPs as it followed only pseudo-second model.